Development and Testing of the Provider and Staff Perceptions of Integrated Care (PSPIC) Survey. (December 2019) - Derrett, Sarah; Gunter, Kathryn E.; Samaranayaka, Ari; Singer, Sara J.; Nocon, Robert S.; Quinn, Michael T.; Breheny, Mary; Campbell, Amanda; Schaefer, Cynthia T.; Heuer, Loretta J.; Chin, Marshall H.
This article discusses development and testing of the Provider and Staff Perceptions of Integrated Care Survey, a 21-item questionnaire, informed by Singer and colleagues' seven-construct framework. Questionnaires were sent to 2, 936 providers and staff at 100 federally qualified health centers and other safety net clinics in 10 Midwestern U.S. states; 332 were ineligible, leaving 2, 604 potential participants. Following 4 mailings, 781 (30%) responded from 97 health centers. Item analyses, exploratory factor analysis, and confirmatory factor analysis were undertaken. Exploratory factor analysis suggests four latent factors: Teams and Care Continuity, Patient Centeredness, Coordination with External Providers, and Coordination with Community Resources. Confirmatory factor analysis confirmed these factor groupings. For the total sample, Cronbach's alpha exceeded 0.7 for each latent factor. Descriptive responses to each of the 21 Provider and Staff Perceptions of Integrated Care questions appear to have potential in identifying areas that providers and staff recognize as care integration strengths, and areas that may warrant improvement.